(untitled) (Indian Journal of Child Health, 2018)
Background: Breast massage is known to increase the volume of breast milk. This is known to occur through stimulation of oxytocin and prolactin. None of the studies have been done which looked at the local effects of breast massage. Objective: The objective was to study the impact of unilateral breast massage on breast milk output among postnatal mothers. Materials and Methods: This quasi-experimental study was conducted in a tertiary health-care hospital, Telangana. Postnatal mothers who approached the center’s milk bank for expressing breast milk were included in the study. The enrolled mothers were shown video of breast massage and also demonstrated the technique of breast massage using breast module by the lactational counsellors of the milk bank, at the hospital in Hyderabad. All the mothers were asked to do massage to the left breast for 10 min and later were asked to express breast milk separately from both breast using electrical hospital grade breast pump. The volume of milk produced from both the breasts was recorded separately at the third session. Results: A total of 42 postnatal mothers were enrolled in the study. The median volume of breast milk expressed from the left breast after breast massage was 22.5 ml (10,30) and the median volume of breast milk expressed from the right breast without breast massage was 15 ml (10,25). The volume of breast milk produced from the side of breast massage was significantly higher when compared to unmassaged side with p<0.001. Conclusion: Breast massage increases the volume of breast milk production. If this increase in breast milk production is due to oxytocin and prolactin, then breast massage on one side should have its effect equally on both the breasts. However, in our study, the volume of milk produced on the massaged side was significantly higher than the unmassaged side. Hence, apart from oxytocin and prolactin, there may be some other local factors responsible for increased milk secretion which requires further research.